Concentrations of plant mineral nutrients and potentially toxic elements in some medicinal plants in the Asteraceae, Fabaceae, and Lamiaceae families from Southern Türkiye: insights into health implications - ÖZYİĞİT, İBRAHİM İLKER (My University, 2023)
Medicinal plants have been used throughout history in the treatment of many diseases in traditional Anatolian folk medicine as well as all over the world. The rapid increase in agricultural and industrial activities due to the increasing population around the world causes air, water and soil pollution, and accumulation of potentially toxic elements in medicinal plants. In this study, plant mineral nutrients and potentially toxic elements analyzes were carried out in 38 plant species belonging to the medicinally important families Asteraceae, Fabaceae and Lamiaceae. The percentage of macroelements (in %) varies between 0.20 and 1.46 for calcium, 0.08 and 1.35 for potassium, 0.04 and 0.24 for magnesium, 0.01 and 0.34 for sodium, while concentrations of microelements and potentially toxic elements (in mg kg−1) vary between 3.21 and 721.28 for aluminum, 41.33 and 231.01 for boron, 0.01 and 0.61 for cadmium, 1.09 and 47.79 for chromium, 12.90 and 43.13 for copper, 17.75 and 1109.39 for iron, 51.50 and 715.48 for manganese, 0.12 and 9.42 for nickel, 1.58 and 22.11 for lead and finally 80.82 and 260.08 for zinc. In addition, estimated daily intake (EDI), target hazard quotient (THQ), and hazard index (HI) for potentially toxic elements, and Recommended Dietary Allowance (RDA) values for mineral nutrients were calculated. In some samples in industrial and mining areas, accumulation of some potentially toxic elements was slightly above the permissible limits set by the World Health Organization (WHO). In Summary, the importance of collecting medicinal plants from protected areas such as mountainous rural areas, far from mining, close to clean rivers, and regular control of values with potentially toxic elements analyzes for human health has been understood once again.
Keywords: Fizik; Atom ve Molekül Fiziği; Kimya; Analitik Kimya; Fizikokimya; Spektroskopi; Temel Bilimler; Physics; Atomic and Molecular Physics; Chemistry; Analytical Chemistry; Physical Chemistry; Spectroscopy; Natural Sciences; Temel Bilimler (SCI); KİMYA, ANALİTİK; SPEKTROSKOPİ; FİZİK, ATOMİK, MOLEKÜLER VE KİMYASAL; Natural Sciences (SCI); CHEMISTRY; PHYSICS; CHEMISTRY, ANALYTICAL; SPECTROSCOPY; PHYSICS, ATOMIC, MOLECULAR & CHEMICAL; Fizik Bilimleri; Atom ve Moleküler Fizik ve Optik; Physical Sciences; Atomic and Molecular Physics, and Optics; Dietary intake; ethnobotany; human health risk; phytoaccumulation; trace element